MEDIA UBI NUABOSI DAN UBI KUNING (Manihot utilissama) SEBAGAI SUBSTITUSI PADA PERTUMBUHAN BAKTERI Escherichia coli DAN Staphylococcus aureus - Agnensia Samma Djala; Michael Bhadi Bia; Norma Tiku Kambuno (Journal of Indonesian Medical Laboratory and Science, 2023)
Indonesia has natural wealth with its biodiversity, UNESCO also declared Indonesia as the 2nd megabiodiversity country after Brazil. The number of natural resources that have been used as a substitute for bacterial growth media encourages researchers to study and create alternative media to replace nutrient agar derived from nuabosi cassava and yellow cassava. This study aims to determine the media of nuabosi cassava and yellow cassava can be used as an alternative to nutrient agar media for the growth of Escherichia coli and Staphylococcus aureus bacteria. This study is a true experimental study with a posttest-only control design where the effect of treatment is analyzed using a different test, namely the one way ANOVA test. The results showed the average number of colonies growth of Escherichia coli bacteria on nuabosi cassava media was 530 CFU/mL, yellow cassava media 599 CFU/mL, and nutrient agar medium as a control was 435 CFU/mL, while for Stapylococcus aureus which was grown on nutrient agar media as control as much as 708 CFU/mL, nuabosi cassava media 434 CFU/mL, and yellow cassava media 103 CFU/mL. The results of the one way ANOVA statistical test on the growth of Escherichia coli bacteria on nuabosi cassava, yellow cassava, and nutrient media in order to obtain a p value of 0.059 (p > 0.05) this indicates that there is no significant difference, which means either yellow cassava media , nuabosi cassava media and nutrient agar media had the same ability on the growth of Escherichia coli bacteria, while the one way ANOVA statistical test for the growth of Staphylococcus aureus bacteria on nuabosi cassava media, yellow cassava media, and nutrient media in order to obtain a significance value of 0.000 ( p < 0.05), it shows that there is a significant difference. Based on the results of the analysis on yellow cassava media and nuabosi cassava media, it can be used as an alternative medium to replace the growth of Escherichia coli and Staphylococcus aureus bacteria.